The Influence of Accountability, Participation, and Transparency of Boss Funds on the Financial Performance of Public Elementary Schools in Palembang City - Putri, Dela Septiani; Saftiana, Yulia; Siddik, Saadah; Kushendar, Kushendar (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study examines and analyzes the effect of accountability, participation, and transparency of boss funds on the financial performance of public elementary schools in Palembang City. The data used are primary data with a population of all public elementary school financial treasurers in the city of Palembang, as many as 251 people; the sampling method uses probability sampling with the sampling technique, namely simple random sampling, so the study uses 72 people as the research sample. The analysis technique used is quantitative with an analytical tool, namely multiple linear regression. The results showed that accountability and transparency of boss funds had a positive and significant effect on the financial performance of elementary schools. In contrast, participation had a negative and insignificant effect on the financial performance of elementary schools.